STRATEGI PEMBERDAYAAN MASYARAKAT: STUDI KASUS STRATEGI DAN KEBIJAKAN PEMBERDAYAAN MASYARAKAT DI KABUPATEN BEKASI - Sopandi, Andi (KYBERNAN: Jurnal Ilmiah Ilmu Pemerintahan, 2010)
Community empowerment strategy is a step that needs to be done by analyzing the potentials and problems in a particular community. It also needed to determinestrategies and policies by basing themselves on four domain of Community Development, namely: (1) Populist Aspects; (2) the aspect of self-reliance, (3) Aspects of Independence, and (4) Aspects of sustainability (Sustainable). This is an ideal formulation to obtain the model of effective community empowerment strategies